Emo-Demo “Air Bersih, Hidup Berseri” sebagai Edukasi MCK Sehat di Desa Mandiro - ningtyias, farida wahyu; Nurhalisa, Siti; Wahyuny, Aprillya; Pratiwi, Farika Nadiya; Nurhansyah, Nimas Oktarisa; Imamah, Dina Yusrotul; Lestari, Yunita Dwi; Jannah, Hanifah Raudhatul (Jurnal of Community Health Development, 2025)
Background: Stunting is a growth problem caused by long-term malnutrition that occurs within the first 1000 days of life, and accumulation of the effects of inadequate nutritional intake and infections during pregnancy is a the causes of child malnutrition. The impact from low levels sanitation is reducing the quality of life of the community, one of the causes of stunting. The water quality for daily needs must meet the requirements so as not to cause stunting. The Emo-Demo activity with the theme of clean living water in Mandiro Village aims to increase the understanding of pregnant women about the importance of using clean water for daily needs. Methods: The Emo-Demo activity with the theme “Clean Water, Radiant Life” was held on Monday, December 9, 2024, located in Mandiro Village, Tegalampel District, Bondowoso Regency. The targets of this Emo-Demo were 15 pregnant women. The method of this activity starts from the preparation stage including coordination, implementation of Emo-Demo, and evaluation. The results of correct and incorrect answers in pre-test and post-test were calculated manually. To determine the increased knowledge of the participants a paired sample t-test was used. Results: From the results of the data analysis, there was a significant increase of 13% in the understanding of mothers of toddlers about clean water in preventing stunting. The result of the pre-test calculation was 62.8%, while the post-test obtained an average result of 92.4%. Conclusion: Emo-Demo activity in Mandiro Village, pregnant women received new information that touched their emotions, so they would change their habits and minimize using river water.